Changes in Alcohol Use and Drinking Context due to the COVID‐19 Pandemic: A Multimethod Study of College Student Drinkers. (23rd March 2021) - Jackson, Kristina M.; Merrill, Jennifer E.; Stevens, Angela K.; Hayes, Kerri L.; White, Helene R.
Abstract : Background: In spring 2020, U.S. universities closed campuses to limit the transmission of COVID‐19, resulting in an abrupt change in residence, reductions in social interaction, and in many cases, movement away from a heavy drinking culture. The present mixed‐methods study explores COVID‐19‐related changes in college student drinking. We characterize concomitant changes in social and location drinking contexts and describe reasons attributed to changes in drinking. Methods: We conducted two studies of the impact of the COVID‐19 pandemic on drinking behavior, drinking context, and reasons for both increases and decreases in consumption among college students. Study 1 (qualitative) included 18 heavy‐drinking college students ( M age  = 20.2; 56% female) who completed semi‐structured interviews. Study 2 (quantitative) included 312 current and former college students who reported use of alcohol and cannabis ( M age  = 21.3; 62% female) and who completed an online survey. Results: In both studies, COVID‐19‐related increases in drinking frequency were accompanied by decreases in quantity, heavy drinking, and drunkenness. Yet, in Study 2, although heavier drinkers reduced their drinking, among non‐heavy drinkers several indices of consumption increased or remained stable . Both studies also provided evidence of reductions in social drinking with friends and roommates and at parties and increased drinking with family. Participants confirmed that their drinking decreased due to reduced social opportunities and/or settings, limited access to alcohol, and reasons related to health and self‐discipline. Increases were attributed to greater opportunity (more time) and boredom and to a lesser extent, lower perceived risk of harm and to cope with distress. Conclusion: This study documents COVID‐19‐related changes in drinking among college student drinkers that were attributable to changes in context, particularly a shift away from heavy drinking with peers to lighter drinking with family. Given the continued threat of COVID‐19, it is imperative for researchers, administrators, and parents to understand these trends as they may have lasting effects on college student drinking behaviors. Abstract : This mixed‐method study explored COVID‐19‐related changes in college student drinking using a combination of interviews ( n =18) and online surveys ( n =312). Increases in drinking frequency were accompanied by decreases in quantity, heavy drinking, and drunkenness, especially among heavier drinkers. Drinking reductions were attributable to changes in context, particularly shifts from social drinking with peers to lighter drinking with family; participants also reported changes in access, opportunity, and risk of harm. These COVID‐19‐related changes may have lasting effects on college student drinking.